PENGARUH KOMPENSASI, PENGEMBANGAN KARIR, LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN KARANGANYAR DENGAN KEYAKINAN DIRI (SELF EFFICACY) SEBAGAI VARIABEL PEMODERASI - Fathonah, Siti; Utami, Ida (-)
This research aims to know: 1) the influence of a compensation toward the employees a job satisfaction, 2) the influence of a carrier development toward the employees a job satisfaction, 3) the influence of a job environment toward the employees a job satisfaction, 4) the influence of an organization commitment toward the employees a job satisfaction, 5) self efficacy in the moderating influence of a compensation toward employees a job satisfaction, 6) self efficacy in the moderating influence of a carrier development toward employees a job satisfaction, 7) self efficacy in the moderating influence of a job environment toward employees a job satisfaction, 8) self efficacy in the moderating influence of an organization commitment toward employees a job satisfaction. The data are collected from 60 employees by using a random sampling method. They are analyzed through the research instruments such as a product moment test and the reliability test by using a Cronbach Alpha technique; assumption classical such as a normality, autocorrelation, heteroscedastisity test and multicolinierity test; hypothesis test such as multiple linier regression with interactive test, t test, F test and determination coefficient (R2). The research result shows that: 1) the influence positive and significant of a compensation toward the employees a job satisfaction, 2) the uninfluenced of a carrier development toward the employees a job satisfaction, 3) the influence positive and significant of a job environment toward the employees a job satisfaction, 4) the influence positive and significant of an organization commitment toward the employees a job satisfaction, 5) the self efficacy uninfluenced in the moderating of a compensation toward employees a job satisfaction, 6) the self efficacy uninfluenced in the moderating of a carrier development toward employees a job satisfaction, 7) the self efficacy uninfluenced in the moderating of a job environment toward employees a job satisfaction, 8) the self efficacy uninfluenced in the moderating of an organization commitment toward employees a job satisfaction Key word: compensation, carrier development, job environment, organization commitment, self efficacy, job satisfaction